Evaluación de la capacidad antioxidantes de extractos acuosos de curcuma (Longa linn),aplicados en la elaboración de salsa de tomate , Machala 2014. - Correa Loarte, Diana Cristina (2015)
The aim of this research is to determine the antioxidant capacity of Turmeric rhizome (Longa linn) for different antioxidants resource. Turmeric (Curcuma longa linn) had a moisture content of 9.25% ash 10.41% total solids 90.75% 7.10 pH resulting in a percentage for the color of 234,19%. antioxidant capacity in vitro rhizome powder and methanol extracts of Turmeric (Curcuma longa linn) was evaluated in a tomato sauce resulting in a percentage of scavenging activity of 88.44% DPPH radical although there are many methods for measuring capacity antioxidant of a species or substance, the antioxidant capacity with the most commonly used method was determined and is based on the stability of the radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) which is attributed to the delocalization of the unpaired electron, this relocation also gives a violet coloration characterized by an absorption band in ethanol solution, centered around 520 nm measured in a spectrophotometer. It indicated a concentration of 0.39 mg / L Ac. Asc.